Impact on Agriculture and Medicinal Factors Amid COVID-19 in India - Kumar, Vinit; Purohit, Mihir (Journal of Advanced Research in Service Management, 2022)
The ongoing health crisis of COVID-19 has affected almost all walks of life. Protecting the lives of people suffering from the disease and frontline health responders have been the priority of the nation. Governments have started actions in full swing since the corona virus attack created an unprecedented situation. India declared a three-week nationwide lockdown till mid-April in the initial phase, which was subsequently extended for achieving satisfactory containment of the virus spread.